2008
DOI: 10.1007/s11553-008-0125-1
|View full text |Cite
|
Sign up to set email alerts
|

Messung der motivationalen Bereitschaft zu körperlicher Aktivität

Abstract: Die Förderung körperlicher Aktivität hat eine hohe Public-Health-Relevanz. Bereits bei Kindern und Jugendlichen wirkt körperliche Aktivität präventiv [30]. Die Prävalenz ausreichender körperlicher Aktivität scheint dagegen eher gering. Im Jugendalter sinkt zudem das Aktivitätsaus-maß deutlich ab [12,25]. Um die körper-liche Aktivität evidenzbasiert zu fördern, wird eine theoretische Fundierung gefordert [11]. Das transtheoretische Modell der Verhaltensänderung (TTM) ist ein international etabliertes Modell, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In future investigations, it would be desirable to complement self-report measures of physical activity with objective measures, for example, accelerometry. Regarding sex differences, the present study found the male sex to be related to greater levels of physical activity, which is consistent with previous findings [20][21][22][23][24][25], indicating that attempts to reduce obstacles to physical activity should target girls in particular. With regard to the examination of experiences and impact of weight-related teasing for boys and girls separately, the present results provide some new information: While boys reported lower physical activity levels associated with weight teasing, girls did not, although weight teasing has been found to be associated with lower physical activity in girls earlier [3].…”
Section: Hierarchical Stepwise Regression Analysis On Self-efficacysupporting
confidence: 92%
See 1 more Smart Citation
“…In future investigations, it would be desirable to complement self-report measures of physical activity with objective measures, for example, accelerometry. Regarding sex differences, the present study found the male sex to be related to greater levels of physical activity, which is consistent with previous findings [20][21][22][23][24][25], indicating that attempts to reduce obstacles to physical activity should target girls in particular. With regard to the examination of experiences and impact of weight-related teasing for boys and girls separately, the present results provide some new information: While boys reported lower physical activity levels associated with weight teasing, girls did not, although weight teasing has been found to be associated with lower physical activity in girls earlier [3].…”
Section: Hierarchical Stepwise Regression Analysis On Self-efficacysupporting
confidence: 92%
“…family and peer groups, on self-efficacy [2,11,12] and physical activity in youth [13][14][15][16][17][18][19]. According to sports sciences, girls were found to be less physically active than boys [20][21][22][23][24][25]. Nevertheless, across different age groups, girls especially were found to gain from parental and friends' support with regard to their self-efficacy beliefs and physical activity levels [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Five of the ten processes of change had lower values than conventionally acceptable and have to be interpreted with caution. The validity of the staging algorithm remains vague because we only examined the association between the stages, physical activity, and a sedentary lifestyle by self‐report (Bucksch & Finne, 2008). Hagler et al .…”
Section: Discussionmentioning
confidence: 99%
“…Five of the ten processes of change had lower values than conventionally acceptable and have to be interpreted with caution. The validity of the staging algorithm remains vague because we only examined the association between the stages, physical activity, and a sedentary lifestyle by self-report (Bucksch & Finne, 2008). Hagler et al (2006) validated a similar physical activity staging algorithm against accelerometer data and found inconsistent construct validities among the sexes and different age groups.…”
Section: Rodgersmentioning
confidence: 99%
“…This model was originally developed by Prochaska and DiClemente in the context of smoking cessation in 1983 [ 32 ]. It was then applied to physical activity by Marcus et al [ 14 ] and validated in multiple studies [ 33 , 34 ]. According to the model, the course of behavioural change can be conceptualized as a transition through the stages of precontemplation , contemplation , preparation , action , and maintenance [ 32 ].…”
Section: Introductionmentioning
confidence: 99%